Barriers and Facilitators of Physical Activity - Mbabazi, Johnson; Kanmodi, Kehinde Kazeem; Kunonga, Edward; Tolchard, Barry; Nnyanzi, Lawrence Achilles (Journal of Health and Allied Sciences NU, 2022)
Background Physical inactivity accounts for 16.6% of deaths in the United Kingdom. This study aims to review the recent (2016–2021) systematic reviews (SRs) on the facilitators and barriers to physical activity (PA) participation among (UK)-based adults.Methods Using the Participants, Interventions, Comparators, and Outcomes framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses strategy, a SR of SRs of studies on the facilitators and barriers to PA among (UK)-based adults, published between 2016 and December 3, 2021, in the PubMed, SCOPUS, or Cochrane Database of Systematic Reviews, was done.Results Three SRs (each published in 2016, 2019, and 2021) were included and reviewed in the study. None of the reviewed SR included a study conducted during the coronavirus disease 2019 (COVID-19) pandemic; also, a paucity of primary studies on PA among (UK)-based adult black, Asian, and ethnic minorities populations was recorded. Having a knowledge/appreciation of the benefits of PA, having the opportunity for social interaction/participation and PA-related support, and having a safe environment for PA were the persistently reported facilitators to PA among (UK)-based adults. On the other hand, having language difficulties/language barrier, lack of time, and having underlying health problems were the persistently reported barriers to PA among them. Not all the included SRs received project funding.Conclusion The outcomes of this study had identified contemporary research gaps regarding the current challenges related to PA among (UK)-based adults. It is a fact that COVID-19 has come to stay in the (UK) and, as a result, it has affected ways of living, especially PA; hence, there is an imminent need for a SR to collate current primary evidence, with regards to the COVID-19 pandemic, on the facilitators and barriers of PA among (UK)-based adults.
Keywords: barriers; facilitators; physical activity; adult; UK; review; COVID-19